Answer
x = 6
y = -11
Step-by-step
To solve the system of equations, i just need to substitute the value of one variable into the other equation. I will start by solving for y.
1. Substitute the value for x into the first equation
y = -3(-2y - 16) + 7
2. Use the Distributive Property of Multiplication to get rid of the parentheses
y = 6y + 48 + 7
3. Combine like terms
y = 6y + 55
4. Subtract 6y from both sides to get all y values together on one side
y - 6y = 6y + 55 - 6y
5. Simplify
-5y = 55
6. Divide both sides by -5 to find the value of y
-5y / -5 = 55 / -5
7. Simplify
y = -11
Part 2: Substitute the value for y into the second equation and solve for x
1. Substitute
x = -2(-11) - 16
2. Multiply
x = 22 - 16
3. Subtract
x = 6
Part 3: State your answer
x = 6
y = -11
I hope this helps!